Pretreatment prognostic nutritional index as a prognostic marker in head and neck cancer: a systematic review and meta-analysis - Chih-Wei Luan (Nature Portfolio, 2021)
Abstract The predictive value of the pretreatment prognostic nutritional index (PNI) for head and neck cancer (HNC) remains controversial. We conducted a meta-analysis to assess the predictive value of PNI in HNC patients. A systematic search through internet databases including PubMed, Embase, and Cochrane Library for qualified studies estimating the association of PNI with HNC patient survival was performed. Overall survival (OS), progression-free survival (PFS), disease-specific survival (DSS), disease-free survival (DFS) and distant metastasis-free survival (DMFS) data were collected and evaluated. A random-effects model was used to calculate the pooled hazard ratios (pHRs) and corresponding 95% confidence intervals (CIs). A total of 7815 HNC patients from 14 eligible studies were involved. Pooled analysis showed that low pretreatment PNI was correlated with poor OS (pHR: 1.93, 95% CI 1.62–2.30, p < 0.001), PFS (pHR: 1.51, 95% CI 1.19–1.92, p = 0.008), DSS (pHR: 1.98, 95% CI 1.12–3.50, p < 0.001), DFS (pHR: 2.20, 95% CI 1.66–2.91, p < 0.001) and DMFS (pHR: 2.04, 95% CI 1.74–2.38, p < 0.001). Furthermore, low pretreatment PNI was correlated with poor OS despite variations in the cancer site, sample size, PNI cut-off value, analysis method (multivariate analysis or univariate analysis) and treatment modality in subgroup analysis. Elevated pretreatment PNI is correlated with a superior prognosis in HNC patients and could be used as a biomarker in clinical practice for prognosis prediction and treatment stratification.